Geographic Access to Breast Imaging for U.S. Women - Onega, Tracy (2014)
BACKGROUND: The breast imaging modalities of mammography, ultrasound, and magnetic resonance imaging (MRI) are widely used for screening, diagnosis, treatment, and surveillance of breast cancer. Geographic access to breast imaging modalities is not known at a national level overall or for population subgroups. METHODS: A retrospective study of 2004-2008 Medicare claims data to identify ZIP codes in which breast imaging occurred, and data were mapped. We estimated travel times to each modality for 215,798 census block groups in the contiguous U.S. Using Census 2010 data, we characterized travel times by socio-demographic factors for 92,788,909 women aged ≥30 years, overall, and by subgroups of age, race/ethnicity, rurality, education, and median income. RESULTS: Overall, 85% of women had travel times of ≤20 minutes to nearest mammography or ultrasound, and 70% had travel times of ≤20 minutes for MRI with little variation by age. Native American women had median travel times 2-3-fold longer to all three modalities, compared to women of other racial/ethnic groups. For rural women, median travel times to breast imaging were 4-8-fold longer than for urban women. Black and Asian women had shortest median travel times to all three modalities. CONCLUSION: Travel times to mammography and ultrasound breast imaging are short for most women, but to breast MRI travel times are notably longer. Native American and rural women are disadvantaged in geographic access based on travel times to breast imaging. This work informs potential interventions to reduce inequities in access and utilization.